Pomegranate Extract as A Natural Therapy for Preeclampsia: Enhancing Endothelial Function, Modulating Inflammation, and Boosting Antioxidant Activity - Wahyuni, Endang Sri; Soetrisno, Soetrisno; Purwanto, Bambang; Wasita, Brian; Widyaningsih, Vitri; Cilmiaty, Risya; Dirgahayu, Paramasari (Trends in Sciences, 2026)
Preeclampsia is a pregnancy complication characterised by hypertension in which blood flow to the mother and baby is reduced. It significantly affects the health of the mother and foetus and can lead to organ damage. Pomegranates are rich in bioactive compounds, especially polyphenols, which have antioxidant and anti-inflammatory properties, making them a potential therapeutic strategy for preeclampsia. Inflammation, oxidative stress, and autoimmune responses are significant in the pathogenesis of preeclampsia. This study aimed to explore the bioactive compounds in pomegranate (Punica granatum) fruit extract through phytochemical analysis; 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant assays; absorption, distribution, metabolism, excretion, and toxicity (ADMET) prediction; molecular docking; and in silico simulations using molecular targets involved in the pathophysiology of preeclampsia. Pomegranate fruit extract was obtained using a maceration technique. The extract was found to contain high levels of polyphenols, flavonoids, and tannins. It also exhibited strong antioxidant activity, with a half maximal inhibitory concentration of 20.967 (± 0.149) µg/mL. Molecular docking indicated strong binding affinity between luteolin and aschantin and the key targets carbonic anhydrase II, endothelial nitric oxide synthase (eNOS) and nuclear factor kappa-light-chain enhancer of activated B cells (NF-kB), demonstrating their potential reduce oxidative stress and inflammation and improve endothelial function. Our ADMET predictions demonstrated favourable pharmacokinetic properties and low toxicity, supporting the safety of luteolin and aschantin. These findings demonstrate the potential of pomegranate extract as a natural therapeutic agent for the management of preeclampsia and provide a basis for future clinical studies. HIGHLIGHTS Pomegranate extract exhibited high levels of polyphenols, flavonoids, and tannins, with potent antioxidant activity (IC50 20.967 ± 0.149 µg/mL); Luteolin and aschantin compounds within the extract exhibited strong affinities with carbonic anhydrase II, eNOS and NF-kB, supporting the reduction of oxidative stress and inflammation, and the improvement of endothelial function; Molecular docking simulations and ADMET predictions confirmed the therapeutic potential of these compounds, which demonstrated favourable pharmacokinetic characteristics and low toxicity; Pomegranate extract demonstrates potential as a natural therapeutic agent for the management of preeclampsia; This study paves the way for further clinical research. GRAPHICAL ABSTRACT